Pemberdayaan Masyarakat dalam Pencegahan Stunting: Strategi Intervensi Berbasis Kearifan Lokal di Desa Ranah Baru Kecamatan Kampar Kabupaten Kampar - Firdaus, Emilda; Andrikasmi, Sukamarriko; Fitri, Rahmi Pramulia; Hermita, Neni; Mubarak, Mubarak; Jahwara, Ibnu Habib (Unri Conference Series: Community Engagement, 2024)
Stunting is a problem caused by a child's lack of nutritional intake for a long time, resulting in growth disorders in children, namely a height that is lower than the age standard. Based on the results of monitoring nutritional status and measuring stunting at the village level in 2023, it was recorded that in Kampar District, Ranah Baru Village is the village with the largest number of stunted children, namely 5 (five) children. Through the Community Service activities of the Ministry of Education, Culture, Research and Technology, the University of Riau Community Empowerment Scheme (PMM), seeks to carry out various stunting prevention programs and activities to make the village 0 (zero) stunting by increasing the community's knowledge regarding stunting prevention. and increasing self-grown food crops to fulfill children's daily nutrition, organizational management and entrepreneurship training. Not only the community, these programs and activities must also involve various parties and cadres in the village, including the village government, health workers, community leaders and families to work together to prevent and reduce the number of stunted children in the village. The aim of this service is to change people's habitual patterns so that they are more responsive to stunting. As a result of this service activity, the community can utilize all the potential that exists in their village in the form of local wisdom appropriately and wisely so that they can overcome the problem of stunting either before or after